2021
DOI: 10.21203/rs.3.rs-223378/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antitumor Effects of Dihydromyricetin on the Proliferation, Migration and Apoptosis of Human Hepatocellular Carcinoma Hep3B Cells

Abstract: Background: Hepatocellular carcinoma (HCC) represents a serious public health problem worldwide and has high morbidity and mortality. Dihydromyricetin (DHM) exhibits anti-tumor effect on a variety of malignancies, but its antitumor function of DHM in HCC has been unclear. The aim of this study was designed to investigate the antitumor effect of DHM on cell apoptosis, proliferation, migration and invasion of hepatoma carcinoma cells. Methods: Cultured Hep3B cells were treated with different DHM concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Baitouweng decoction is an important prescription for the treatment of gastrointestinal diseases[ 17 , 18 ]. We found that Baitouweng decoction inhibits the proliferation of EC cells[ 19 , 20 ]. However, there is a lack of research on the mechanism of action of this prescription for EC.…”
Section: Introductionmentioning
confidence: 99%
“…Baitouweng decoction is an important prescription for the treatment of gastrointestinal diseases[ 17 , 18 ]. We found that Baitouweng decoction inhibits the proliferation of EC cells[ 19 , 20 ]. However, there is a lack of research on the mechanism of action of this prescription for EC.…”
Section: Introductionmentioning
confidence: 99%